A Response to Snow's Comment on Business Policy Teaching Research - Wolfe, Joseph (Academy of Management Review, 1976)
In this article the author responds to comments made over a research paper that examined the effectiveness of business education. He defends his work noting that the ideal research design will most likely be compromised to some degree and that designing the perfect research instrument is impossible. He also adds that his research was focused on the internal validity of teaching formats while the comments directed at his work were related to the external validity of teaching methods. He recognizes that this is an area that needs research; however, this was not the focus of his work.